Analisis Kemampuan Literasi Numerasi Siswa Pada Tingkat Sekolah Dasar - Sherly Mayfana Panglipur Yekti; iftitaahul Mufarrihah (Institut Agama Islam Negeri Palopo, 2022)
The purpose of the study was to analise numerical literacy of elementary students.This research uses a case study qualitative approach. Data collection techniques with participatory observation, interviews, and documentation. The result of this study areÂ numerical literacy analise of elementary students.